The Changing and Unchanged Nature of Inequality and Seniority in Japan - YAMADA, Ken (Institutional Knowledge at Singapore Management University, 2015)
Wage inequality declined in the 1990s, while it increased in the 2000s for full-time male workers in Japan. We find that a decreased return to firm-specific human capital, which has been neglected in previous empirical analyses of inequality, is a key factor preventing a rise in wage inequality during the prolonged period of economic stagnation, known as Japan’s lost decades. We also find that, while changes in returns to general and specific human capital contributed to narrowing wage inequality in the 1990s and widening wage inequality in the 2000s, a significant fraction of the increase in wage inequality in the 2000s is attributable to composition effects arising from an increased share of educated and experienced workers, among whom wages are more dispersed.